Business to business relationship towards Kahwin2U: a case study of Yata Jasamedia / Nooratikah Tumin - Tumin, Nooratikah (2015)
The business to business relationship is the one important relationship to being built among the business people in order to market their product and services. These relations also will shows how far their product or services have been familiar among the businesses and also customer. In relations with that, this study will focus on the factor of the business to business relationship and make the relationship exist will stay longer. Recent observation in Kahwin2U shows this company has practice the business to business relationship only with the supplier and not between the other businesses. Therefore, this study will find out the factor that influences the business to business relationship in Kahwin2U. The method that been used is data collection were obtained by doing the interviewed with the three respondents, the Director and the staff of Kahwin2U and also the wedding planner as the other businesses. The results find out there are eight factors that influence the business to business relationship. There are mutual benefit, company background, prices, committed, satisfaction, trust, marketing and profit. The researcher also found out there is a gap between the company practice and the journal that been listed. At the end, the researcher will give suggestion ways that can be practice in order to improve the business to business relationship toward Kahwin2U.